Open source Vicon Toolkit for motion capture and Gait Analysis. (November 2021) - Goldfarb, Nathaniel; Lewis, Alek; Tacescu, Alex; Fischer, Gregory S.
Highlights: Open source library for parsing and analyzing Vicon data. Open source library for analyzing Gait data from a mocap. Rigid body analysis for Vicon markers. Joint identification and tracking. Abstract: Background and Objective: The Vicon motion capture system is a popular tool for biomechanics, gait analysis, and robotics. The ASCII files produced are large and complex, making them difficult to read and analyze. Methods: This paper presents two packages, the Vicon Toolkit Package and the Gait Analysis Toolkit Package. They use an open-source framework for ingesting, parsing, and analyzing Vicon mocap data and performing gait analysis. The package that handles the Vicon analysis is separated from the Gait Analysis package to allow for abstraction and expansion, and is not specific only to the Vicon system. Results: Our Vicon Toolkit provides tools to work directly with the marker data and other Vicon Nexus system outputs. The Gait Toolkit provides tools for performing gait analysis, EMG filtering, and learning trajectories. The packages are built upon a core library, GaitCore, that provides unified objects to perform operations and store data. Conclusion: This paper will show how to use the packages' tools and the expected outputs. All the tools are open-source and written in Python3.x for ease of use and access to other powerful libraries.